Technological properties of milks fermented with thermophilic lactic acid bacteria at suboptimal temperature - Moreira, M. (2000)
In the present work the synergistic relationship between different strains of Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus was studied at optimal (44°C) and suboptimal temperatures (30°C). Acidification, viscosity, whey syneresis, and bacterial concentration of the final product were evaluated on single-strain and mixed cultures after 24 h at 30°C and 6 h at 44°C. Three pairs of strains (LBB+CP2, LBP+CP2, and LBR+CP2) showed synergistic effect, which was reflected by the viscosity and syneresis of the coagulum. These results were more significant when cultures were incubated at 30°C, reaching apparent viscosity values of 19 to 28 mPa × s. On the other hand, lactobacilli cultures enhanced the growth of two streptococci strains (CP2 and CP4). These results were confirmed by cultures of streptococci supplemented with supernatants of culture of lactobacilli. Those supernatants stimulate the viscosity produced by CP2 and CP4 strains and reduce the syneresis of all cultures of streptococci. Neither the increase of viscosity nor reduction of syneresis could be attributed to a decrease of pH.